Under the Heel of the Dragon Islam, Racism, Crime, and the Uighur in China. - Kaltman, Blaine (Athens, OH : Ohio University Press, 2014)
The Turkic Muslims known as the Uighur have long faced social and economic disadvantages in China because of their minority status. Under the Heel of the Dragon: Islam, Racism, Crime, and the Uighur in China offers a unique insight into current conflicts resulting from the rise of Islamic fundamentalism and the Chinese government's oppression of religious minorities, issues that have heightened the degree of polarization between the Uighur and the dominant Chinese ethnic group, the Han. Author Blaine Kaltman's study is based on in-depth interviews that he conducted in Chin.
Acknowledgments; 1 Uighur Ethnic Enclaves; 2 Cultural Marginalization and Institutionalization of Blocked Uighur Mobility; 3 Han-Uighur Relations; Gallery; 4 Migration; 5 Living under the Heel of the Dragon; Appendix; Bibliography; Index.
Print version record.
Master record variable field(s) change: 072
Keywords: Uighur (Turkic people) -- China; Muslims -- China; Freedom of religion -- China; China -- Ethnic relations; China -- Ethnic relations; Freedom of religion -- China; Muslims -- China; Uighur (Turkic people) -- China; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Ethnic relations; Freedom of religion; Muslims; Uighur (Turkic people); China; RELIGION / Islam / General; Electronic books